Evaluation of Strategic Intelligence on Countering Smuggling Threats Using High Speed Craft - Nuga Setiawan, Danang; Hanita, Margaretha; Daryanto, Eko (Pelopor Publikasi Akademika, 2024)
This research is based on the increasing threat of sedimentation in water areas by utilizing technological developments through the use of High Speed Crafts (HSC). The increase in threats is faced with obstacles for the authorities in balancing surveillance facilities and infrastructure with the technology used by smugglers. In addition, the need for intelligence data that is integrated with all related apparatus also requires a lot of development. This paper uses a qualitative approach. The data used are secondary data derived from related documents from several institutions, mass media articles and literature reviews related to strategic intelligence. Researchers concluded that smuggling using High Speed Crafts (HSC) in Indonesian waters has been frequent for the past few years. In 2019 and 2020, the DJBC and the Ministry of Finance succeeded in uncovering the practice of smuggling using HSC which had the potential to cause considerable state losses related to alleged money laundering crimes. The mode of HSC smuggling is carried out by the ship-to-ship method from large ships. Enforcement is challenged because the surveillance vessel facilities have a capacity that is not faster than the ships owned by the perpetrators, plus the changing point of the HSC of the smugglers spread across Sumatra and Java. An important evaluation of the supervision of smuggling in the HSC mode is at least related to increasing the quantity and capacity of DJBC through human resources and surveillance ship facilities that have capabilities above the facilities owned by smugglers.